To Assess Short Term Outcomes of Ambulatory Selective Varices Ablation Under Local Anesthesia in Primary Varicose Veins - Muhammad Kamil Zulfiquar, Muhammad Awais, Sundas Javeed, Saulat Naeem, Ayesha Waheed, Rizwan Khan, Rooh-Ul-Ain, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Varicose veins are superficial veins that have become enlarged and twisted. A vein that is confined within fascial planes or is buried beneath subcutaneous tissue can carry massive amounts of high-pressure reflux without being visible at all. Aim: To assess the short-term outcomes of Ambulatory Selective Varices Ablation under Local anesthesia in primary varicose veins disease Methods: this is a descriptive case series conducted at department of surgery, Services Institute of Medical Sciences, from December 2018 to June 2019. After fulfill the inclusion criteria, 181 patients were enrolled. Preoperatively, all varicose veins marked but the patient is in standing position as it’s difficult or impossible to identify during recumbent position. A micro incision or puncture is made near the vein after the anesthetic has been administered into the peri-venous tissues. After removing a segment, the surgeon moved along the vein for roughly the similar distance, makes a second incision, then the procedure is repeated until all sections of the varix have been removed, reducing the risk of an inflammatory response from the residual segment thrombosis. Results: In this study the mean age of the patients was 35.03±5.25 years. C2 CEAP classification was noted in 52(28.7%) patients, c3 CEAP classification found in 101(55.8%) patients. The reflux found in 54(29.8%) patients and recurrence noted in 33(18.23%) patients. Conclusion: The conclusion of this study that Ambulatory Selective Varices Ablation under Local anesthesia is a feasible and reliable technique with lower rate of recurrence in patients presented with in primary varicose veins disease.